Care as a commitment of all: a study in a rural settlement - Simone Wunsch; Maria de Lourdes Denardin Budó; Nara Marilene Oliveira Girardon-Perlini; Raquel Potter Garcia; Stefanie Griebeler Oliveira
This study aims to understand the perceptions of care of families living in a rural settlement in the northwestern area of Rio Grande do Sul. It is an ethnographical based qualitative field research, which has used the Observation-Participation-Reflection Model for data collection, performed between February and March, 2011. The data analysis went through four steps: raw data collection and documentation, describers and indexes identification, contextual and current patterns analysis, and identification of research themes and relevant findings. The study has shown that, for the settlers who participated in the study, care is bound to their vision of world, meaning a commitment of everybody, under the collective and individual premise of improvement of their lives. It is concluded that Nursing needs to understand cultural behaviors in order to enable a congruent and holistic care.